Cooperation with Externalities and Uncertainty - Helga Habis; Dávid Csercsik (Lund University, School of Economics and Management, Department of Economics, 2012)
We introduce a new class of cooperative games where the worth of a coalition depends on the behavior of other players and on the state of nature as well. We allow for coalitions to form both before and after the resolution of uncertainty, hence agreements must be stable against both types of deviations. The appropriate extension of the classical core concept, the Sustainable Core, is defined for this new setup to test the stability of allocations in such a complex environment. A prominent application, a game of consumers and generators on an electrical energy transmission network is examined in details, where the power in- and outlets of the nodes have to be determined in a way, that if any line instantaneously fails, none of the remaining lines may be overloaded. We show that fulfilling this safety requirement in a mutually acceptable way can be achieved by choosing an element in the Sustainable Core.
Keywords: C71; C73; D62; L14; L94; 330; partition function form games; uncertainty; core; sustainability